House Privilege - Lawson, Michael, 1948- (Lawson, Michael, 1948- Joe DeMarco thriller., 2020)
"The fourteenth novel in Mike Lawson's acclaimed series takes political fixer Joe DeMarco to Boston and beyond, to expose an embezzler and the lengths to which she'll go to protect her wealth."--Provided by publisher.